The Collapse of Higher Education in Wartime Sudan - Baleela, Rania; Abugabr Elhag, Husam Eldin E. (International Higher Education, 2025)
The ongoing war in Sudan since April 15, 2023, has resulted in the worst humanitarian crisis in the world today, one characterized by famine, insecurity, genocide, and displacement. In addition to the obvious contemporary toll on the country, this war has overshadowed future generations by severely damaging the physical infrastructure of higher education, jeopardizing long-term prospects for peace, development, and intellectual sovereignty even in the post-war era.